The EU in International Sports Governance A Principal-Agent Perspective on EU Control of FIFA and UEFA - Geeraert, Arnout; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book analyses the levels of influence that the European Union (EU) has over sport governing bodies (SGBs). Contrasting with the US authorities' decisive action, the EU seemed largely absent from the 2015 FIFA corruption saga. Even though the EU has established itself as an actor in its own right in international sports governance, there is still a lack of clarity over its capabilities to control SGBs. By employing a triangular principal-agent model, and by focusing on the case of EU control of FIFA and UEFA, the author demonstrates that the EU holds significant opportunities to control SGBs through both law and policy. There are, however, important limits as well. EU institutional features complicate control, but do not render the EU powerless. Most importantly, though, SGBs can deploy a variety of strategies to mitigate control. In considering these strategies and their effects on the EU's influence, this book provides an informed analysis that will particularly appeal to students and scholars of the EU, sports organizations, and global governance. .
Keywords: Political science; European Union; International relations; Sports; Political Science and International Relations; International Relations; European Union Politics; Political Science; Popular Science in Sports; Electronic books